Tunable Passively-Synchronized 1-μm Q-Switched and 1.5-μm Gain-Switched Dual-Wavelength Fiber Laser Based on an Er/Yb Codoped Fiber - Chunyu Guo; Weiqi Liu; Shuangchen Ruan; Jun Yu; Yewang Chen; Peiguang Yan; Jinzhang Wang; Saurabh Jain; Ping Hua (IEEE Photonics Journal)
A wavelength-tunable passively-synchronized 1-μm Q-switched and 1.5-μm gain-switched dual-wavelength pulsed fiber laser has been demonstrated with a single gain fiber for the first time to our knowledge. The realized dual-wavelength co-oscillation is based on a dual ring-cavity configuration with a common Er/Yb co-doped fiber (EYDF). The Q-switched 1-μm pulses are generated through the saturable absorption effect of unpumped EYDF aided by a 1.5-μm oscillation cavity, whereas the 1.5-μm pulses are produced by the gain-switching of Er3+ ions induced by the 1-μm Q-switched pulses. A tuning range of 11.7 nm from 1045.3 to 1057 nm and 29.7 nm from 1535 to 1564.7 nm are obtained at stable synchronized pulse operation for 1 and 1.5-μm spectral bands, respectively.